Multidisciplinary perspectives on multilingualism the fundamentals - Montanari, Simona (Linguist); Quay, Suzanne (Language contact and bilingualism ;, 2019)
Multilingualism is a typical aspect of everyday life for most of the world's population; it has existed since the beginning of humanity and among individuals of all backgrounds. Nonetheless, it has often been treated as a variant of bilingualism or as a phenomenon unique to individual areas of study. The purpose of this book is to review current knowledge about the acquisition, use and loss of multiple languages using a multidisciplinary perspective, highlighting the common themes and stimulating insights that can emerge when multilingualism is viewed from different but related areas of investigation. The chapters focus on research evidence, showing that multilingualism is a complex phenomenon that involves a myriad of linguistic and extra-linguistic forces and that should be studied in its own right as evidence of human potential and capacity for language. The book is primarily addressed to students and scholars interested in deepening their understanding of the different facets of multilingualism, including the individual and societal circumstances that contribute to it, the cognitive and neural mechanisms that make it possible, and the dynamics involved in the acquisition, use and loss of multiple languages. -- Provided by publisher